2012
DOI: 10.1007/s10067-012-2059-4
|View full text |Cite
|
Sign up to set email alerts
|

A safety analysis of oral prednisone as a pretreatment for rituximab in rheumatoid arthritis

Abstract: The administration of 100 mg of methylprednisolone intravenously (IV) 1/2 h prior to rituximab decreases the incidence of acute infusion reactions (AIRs). However, this pretreatment adds considerable time and conveys potential risk. We performed an open-label prospective assessment of oral prednisone as a pretreatment to rituximab. This was a 26-week open-label trial of 40 mg of oral prednisone given 1/2 h prior to rituximab as a prophylaxis against AIRs in patients with rheumatoid arthritis (RA). The primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Drug and nondrug consumables. Medical consumables used at each stage in the preparation and administration of rituximab were costed according to the acquisition cost to MGH, except for drug costs, for which data from the Federal Supply Schedule (FSS) federal contract service were used (24,25). For the base-case analysis, we used aggregated data from the MGH Medical Infusion Pharmacy to estimate the preparation time of each dose of rituximab and assumed that all time indicated for preparing and checking the drug by a pharmacy technician and a pharmacist, respectively, was dedicated to the preparation of one dosage of rituximab.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug and nondrug consumables. Medical consumables used at each stage in the preparation and administration of rituximab were costed according to the acquisition cost to MGH, except for drug costs, for which data from the Federal Supply Schedule (FSS) federal contract service were used (24,25). For the base-case analysis, we used aggregated data from the MGH Medical Infusion Pharmacy to estimate the preparation time of each dose of rituximab and assumed that all time indicated for preparing and checking the drug by a pharmacy technician and a pharmacist, respectively, was dedicated to the preparation of one dosage of rituximab.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding drug administration, we 1) considered the impact of substituting 60 mg of oral prednisone for 125 mg of intravenous methylprednisolone, which would reduce the chair time because it can be taken at home prior to arriving, therefore saving approximately 30 minutes of chair time while waiting for the steroid to have effect (26); 2) varied the infusion time for the subsequent, shorter dose because faster infusion protocols (approximately 90 minutes vs 120 minutes) have been shown to be safe for subsequent rituximab infusions (4,11‐13); 3) evaluated the impact of using lower doses of rituximab, which have been found to have similar effectiveness as ordinary doses of rituximab (27); 4) considered the impact of biosimilar rituximab, which is approved by the US Food and Drug Administration and assumed to cost less relative to originator rituximab but is not yet marketed (8‐10,28); and 5) substituted a subcutaneous injection of rituximab in place of the second infusion and varied the cost estimates relative to the FSS cost for subcutaneous rituximab as listed for oncology indications. Subcutaneous injections are approved for oncology indications and require only a 30‐minute visit (per MGH's oncology practice).…”
Section: Methodsmentioning
confidence: 99%
“…As advised by the American College of Rheumatology, the Health Assessment Questionnaire (HAQ) has been thoroughly validated and measured in most RA trials [33] . The scale contains 20 questions about daily activities such as dressing, brushing, getting up, eating, strolling, maintaining personal hygiene, touching, and holding [34] .…”
Section: Quality Of Lifementioning
confidence: 99%
“…Alternatively, Carter el at. (18) suggested that a smaller dose of oral prednisone may be as efficacious and well tolerated, and could decrease the administration time.…”
Section: Administration and Efficacymentioning
confidence: 99%